Generative AI and academic skills support at UCL: an institutional approach (Journal of EAHIL, 2024)
The release of OpenAI’s ChatGPT-3.5 to the public in November 2022 marked the beginning of a new era in which generative AI (GenAI) tools are widely available. This has prompted a need for academic skills support for students’ use of GenAI in Higher Education. This article outlines UCL’s approach to developing this support, with a particular focus on referencing and acknowledging GenAI. It includes achievements to date, current initiatives and discussion on challenges and perspectives for the future.